Pengaruh Store Atmosphere, Service Quality, and Customer Satisfaction on Repurchase Intention di Kedai Dimensi Kopi Trawas - Putri, Inas Adilah; Winarno, Sri Tjondro; Widayanti, Sri (International Journal of Multidisciplinary Research and Literature, 2024)
One business venture proliferating in the globalization era is the coffee shop. It can be seen from the many coffee shops that have sprung up, with differences in interesting concepts and variations from the interior design of the cafe and the products offered. One []coffee shop with a unique idea of selling customized roasted coffee beans is Kedai Dimensi Kopi Trawas, located in Trawas, Mojokerto, Indonesia. This unique concept can drive shop sales by producing up to 150 kg of coffee beans. However, there appears to have been a slowing down of coffee bean production to 100 kg. Based on the pre-research interview with the customers who bought Kedai Dimensi Kopi Trawas’s roasted beans, 60% of them did not intend to repurchase. Therefore, researchers are interested in analyzing Kedai Dimensi Kopi Trawas’s store atmosphere, service quality, and customer satisfaction with repurchase intention. Using purposive sampling, we gathered data from 50 Kedai Dimensi Kopi Trawas’s roast bean customers who have bought coffee beans at least once to fill out a Likert-score type questionnaire through Google Forms. The data analysis used in this study used SEM-PLS analysis with the WarpPLS approach. The results show that store atmosphere has a positive and significant effect on repurchase intention, with a p-value of 0.05. Service quality also positively and significantly affects repurchase intention, with a p-value of 0.01. Likewise, customer satisfaction shows a positive and significant relationship with a p-value <0.01 on repurchase intention. The results of this study indicate that knowing repurchase intention can increase coffee bean sales at Kedai Dimensi Kopi Trawas